The Effect of Genetically Modified Food on Infertility Indices: A Systematic Review Study. (13th August 2020) - Keshani, Parisa; Sharifi, Mohammad Hossein; Heydari, Mohammad Reza; Joulaei, Hassan
Abstract : Background and Objectives . With the increase in the growth of genetically modified (GM) crops, concerns as to the adverse effects of GM crops have risen in the community. The present systematic review seeks to assess the GM plants' potential impacts on the sperm parameters, including sperm head, sperm motility, sperm abnormality, and fertility index. Materials and Methods . A structured literature search was independently performed by three authors on Scopus, Web of Science, PubMed, and Embase in January 2019. A total of 1467 publications were obtained by the search strategy after eliminating the duplicates. Moreover, the review only included articles written in English language. Other pertinent peer-reviewed publications were chosen ("snowballing") from the reference lists in the selected publications. To assess the GM crop effects on infertility, experimental studies designed with the control group were selected. On the basis of abstract screening and full-text reviewing, 39 relevant publications were selected, seven of which were used in our review. To access the quality of articles, we used the Cochrane checklist. The collected articles were scored independently by three authors, and the publications with the eligibility criteria were included in our review. No article was excluded due to quality assessment. Results and Conclusion . Our findings indicated that GM products had no adverse effects on infertility indices such as the sperm head, sperm motility, sperm abnormality, and fertility indices. Long-term research still seems to be strongly necessary to ensure that the use of GM plants does not cause any harm to consumers, especially in infertility area.